Cigarette Smoking Triggers Colitis by IFN-γ+ CD4+ T Cells - Lee, Gihyun; Jung, Kyoung-Hwa; Shin, Dasom; Lee, Chanju; Kim, Woogyeong; Lee, Sujin; Kim, Jinju; Bae, Hyunsu (Frontiers in Immunology, 2017)
The increased incidence of Crohn’s disease in smokers has been recently reported, suggesting a strong association of cigarette smoke (CS) with colitis. However, the mechanism of the action of CS on colitis has not yet been explored. Here, we demonstrate that CS exposure is sufficient to induce colitis in mice. Interestingly, the colitis is mainly mediated by Th1, but not Th17, responses. CD4+ T-cell depletion or T-bet/IFN-γ deficiency protects against the development of colitis induced by CS. Additionally, IFN-γ-producing CD4+ T cells play a substantial role in CS-induced colitis. The adoptive transfer (AT) of effector T cells from CS-exposed WT mice into colitis-prone mice caused these mice to develop colitis, while the AT of effector T cells from IFN-γ knock-out mice did not. These findings have implications for broadening our understanding of CS-induced pathology and for the development of novel therapeutic strategies to treat Crohn’s disease.